Dapper-1 induces myocardial remodeling through activation of canonical wnt signaling in cardiomyocytes - Hagenmüller, Marco; Riffel, Johannes; Bernhold, Elmar; Fan, Jingjing; Zhang, Min; Ochs, Marco; Steinbeisser, Herbert; Katus, Hugo; Hardt, Stefan (Hypertension, 2013)
Heart failure has an increasing contribution to cardiovascular disease burden and is governed by the myocardial remodeling process. The contribution of Wnt signaling to cardiac remodeling has recently drawn significant attention. Here, we report that upregulation of Dapper-1 in a transgenic mouse model activates the canonical/β-catenin-dependent Wnt pathway through dishevelled-2. These mice exhibited increased heart weight/tibia length ratio, myocyte cross-sectional area, and upregulation of hypertrophic marker genes compared with wild-type mice. Furthermore, impairment of left ventricular systolic and diastolic function was observed in all indicating features of myocardial remodeling. Depletion of Dapper-1 and dishevelled-2 in cardiomyocytes demonstrated that Dapper-1 functions upstream of dishevelled-2 and that activity of both Dapper-1 and dishevelled-2 is essential for activating canonical Wnt signaling. Moreover, Dapper-1 depletion alleviated Wnt3a- and phenylephrine-induced cardiomyocyte hypertrophy. These observations provide evidence that Dapper-1-mediated activation of canonical Wnt signaling is necessary and sufficient to induce cardiomyocyte hypertrophy. Inhibition of this pathway may thus serve as a novel therapeutic strategy for alleviating cardiac hypertrophy.
Gesehen am 15.10.2021